Effectiveness of application of apple biological protection systems against green and red-headed apple aphids of the Western Forest Steppe of Ukraine - Hunchak , M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. Research on the effectiveness of apple tree protection systems based on the use of biological preparations against green and red-headed apple aphids in the conditions of the Western Forest Steppe. Methods. The distribution of pests was recorded depending on the phases of apple tree development in accordance with generally accepted methods. The technical efficiency of insecticides was determined after 2 and 7 days. Statistical processing of the results was carried out according to generally accepted methods. Results. During the monitoring of the phytosanitary state, it was established that during 2022—2023, in the conditions of the Western Forest Steppe of Ukraine, significant damage was caused to the agrocenosis of apple trees by green and red-headed apple aphids. The research results established that the application of the bioprotection system of apple plantations No. 1 (Actophyt BT (aversectin C, 0.2%), k.e.; Biospectr BT (Pseudomonas bacteria, titer not lower than 5.0 × 109 CFU/cm3), p.; Bitoxybacillin BT (living cells of Bacillus thuringiensis var. thuringiensis, titer not lower than 2.0 × 109 CFU/ cm3 and spore-crystalline complex with toxins β-exotoxin and δ-endotoxin, r.) provided effectiveness against green apple aphid within 68.4—83.4%, and against red-headed apple aphid — 69.2—75.0%. When applying the following protection system (Bitoxybacillin BT, r. + Biospectr BT, r.; Actofit BT, k.e. + Bitoxybacillin BT, r.; Boverin BT (Beauveria fungi, viable cell titer not lower than 3.0 × 109 CFU/ cm3, p.) effectiveness against green apple aphid was 65.5—80.0%, and against red-headed apple aphid — 63.3—79.2%. Application of bioprotection system No. 3 (Biospectr BT, r. + Actofit BT, k.e.; Metarizin BT (Metarhizium fungi, titer of viable cells not lower than 2.0 × 109 CFU/ cm3), r. + Boverin BT, r.; Bitoxybacillin BT, r. + Biospectr BT, r.) made it possible to reduce the number of green apple aphids by 71.9—83.2% and red-headed apple aphids by 73.1—78.3%. During the study of apple tree protection systems, which were based on the introduction of biopreparts, against green and gray apple aphids in the Western Forest Steppe of Ukraine, the yield was 15.5—15.8 t/ha. Conclusions. All apple bioprotection systems that were studied in the conditions of the Western Forest Steppe of Ukraine ensured high yield rates and a high level of protection of apple plantations against green and red-headed apple aphids. The technical efficiency of the bioprotection systems used against the green apple aphid was 65.5—83.4%, against the red-headed apple aphid — in the range of 63.3—79.2%. The yield of apple plantations during the study of apple tree protection systems, which were based on the use of drugs of biological origin, was 15.5—15.8 t/ha.